Analisis Pelaksanaan Program Pelayanan Nomor Tunggal Panggilan Darurat Muba Siaga 112 di Dinas Komunikasi dan Informatika Kabupaten Musi Banyuasin - Saswita, Saswita; Mudasir, Mudasir; S, Rayani V (@-Publik: Jurnal Administrasi Publik, 2021)
The Muba Siaga 112 Single Number Emergency Call Service is organized by the Musi Banyuasin Regency Government where the Emergency Call Center is the Communication and Information Office of the Musi Banyuasin Regency. With the Muba Siaga 112 Single Number Emergency Call Service Program, it is hoped that it will make it easier for the community in the Musi Banyuasin District to receive emergency services easily and quickly. The purpose of this study was to analyze the implementation of the Muba Siaga 112 Single Number Emergency Call Service Program at the Communication and Information Office of Musi Banyuasin Regency. The analysis technique used in this research is qualitative data analysis technique. This research shows that the overall implementation of the Muba Siaga 112 Single Number Emergency Call Service Program at the Communication and Information Office of Musi Banyuasin Regency has not been carried out optimally. This is due to an obstacle or problem in it. The problem in this study is that in the implementation of emergency services there is still a lack of supporting facilities and infrastructure as well as socialization about Muba Siaga 112 emergency services which are still lacking. Furthermore, the Regional Government of Musi Banyuasin Regency, especially the Communication and Information Office of Musi Banyuasin Regency, is expected to be able to find the right solution to overcome problems that become obstacles or problems in service implementation so that excellent service can be created, namely fast, precise, easy and friendly.